The Impact of the Covid-19 Pandemic on Global Yields: A Short Review of the 2020-2021 Period Monetary and Fiscal Policies’ - Andreea OPREA (Communications of International Proceedings, 2022)
In the period 2020-2021, the global macroeconomic outlook was marked by developments in the Covid-19 pandemic management in general, and the pace of vaccination in particular. The divergence in access to vaccination among developed and emerging economies has segmented the recovery of the economy into two categories, one that followed a smoother path to normalization - as was the case in most developed countries - and the category of countries where recurrent reinfections and their complications prolonged an unfavorable economic climate. Changes in the psychology and consumption patterns induced by the health crisis, such as the increased interest in household goods and products and real estate - especially as a result of migration into the teleworking regime - have favored the emergence of temporary stock deficits, disruptions in chains logistics, and therefore disparities between supply and demand, which have resulted in higher prices. Inflationary pressures were believed to be transitory, so they have generally led to wait and see responses from central banks, which have maintained lax monetary policies aimed at stimulating economic recovery. Should price pressures prove persistent, central banks could accelerate the tightening of monetary policy. However, a premature transition to restrictive monetary measures would make the process of economic recovery more difficult.
Keywords: monetary policy responses; Covid-19 policy responses; FED; ECB; monetary and fiscal policy; government yields; inflation; asset purchase programes